Response of groundwater to the process of reservoirs group regulation and storage in Manas River Basin in Xinjiang - Liu, Bing; Yang, Guang; He, Xinlin (International Journal of Agricultural and Biological Engineering, 2020)
Reservoir regulation and storage is the main approach to alleviate the water pressure caused by the uneven spatial and temporal distribution of surface water resources in arid areas of northwest China. While the regulation and storage of the reservoir affect the conditions of recharge and discharge of groundwater, the process of regional surface-groundwater transformation tends to be complicated. The Manas River basin that lies on the northern slope of Tianshan Mountain in Northwest China was taken in this study as a case. A numerical model of groundwater in basin plain area was established, and the influence of reservoir regulation on groundwater level was studied. The results showed that the total recharge of groundwater in the study area was 75.539 million m3, the total discharge of groundwater was 82.66 million m3, and the groundwater in the study area was in a negative equilibrium state, with a difference of – 69.27 million m3. The water balance method was used to verify the comparison. The total recharge of groundwater was 74.34 million m3, the total discharge of groundwater was 80.726 million m3, and the calculation result of the numerical simulation of the supplementary displacement was 63.82 million m3, basically consistent with the calculation result of the water balance method. The reservoir storage method has obvious changes to the groundwater level around the reservoir. The simulation results of groundwater numerical model showed that when the reservoir was in normal operation, the leakage of the reservoir was 27.35 million m3; when the reservoir was operated at low water level, the leakage of the reservoir was the smallest, 13.47 million m3. The reservoir has the largest amount of leakage of 41.85 million m3 when operated at water storage level. When the reservoir was operated at the lowest water level, the groundwater level around the reservoir was declining compare to the normal operating water level. The maximum drop of the groundwater observation well was 2.1 m, and the maximum monthly average was 0.99 m. When the reservoir was operating at the normal water storage level, the water level of the groundwater around the reservoir has increased compare to the normal operating water level. The maximum increase of the groundwater observation well was 1.5 m, and the maximum monthly average increase was 0.78 m. The influence of the reservoir on the groundwater level was 2000 m upstream and 12000 m downstream. The research conclusions can provide a scientific reference for the development, utilization and management of regional groundwater. Keywords: Manas River Basin, water balance, numerical simulation; reservoir regulating, groundwater DOI: 10.25165/j.ijabe.20201301.4866 Citation: Liu B, He X L. Response of groundwater to the process of reservoirs group regulation and storage in Manas River Basin in Xinjiang. Int J Agric & Biol Eng, 2020; 13(1): 224–233.